2012 IEEE International Topical Meeting on Microwave Photonics 2012
DOI: 10.1109/mwp.2012.6474082
|View full text |Cite
|
Sign up to set email alerts
|

Millimeter wave generation using Brillouin scattering in a high Q fiber ring resonator

Abstract: We introduce an efficient technique to optically generate millimeter-wave sources. The technique is based on the frequency multiplication concept using high order harmonics, generated by a Mach-Zehnder modulator, combined with the Brillouin selective side band amplification process in a high Q fiber ring resonator. We demonstrate the generation of a low phase noise 65.2 GHz signal with a power level 15 dB higher than the power level usually obtained using classical frequency multiplication.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 9 publications
(14 reference statements)
0
3
0
Order By: Relevance
“…Therefore, we have used the BSSA process in the 20m-long FRR to generate high power and high spectral purity millimeter wave signals. This study is well detailed in [12]. Fig.…”
Section: ) Sbs Power Characterizationmentioning
confidence: 96%
See 1 more Smart Citation
“…Therefore, we have used the BSSA process in the 20m-long FRR to generate high power and high spectral purity millimeter wave signals. This study is well detailed in [12]. Fig.…”
Section: ) Sbs Power Characterizationmentioning
confidence: 96%
“…The high Q Opt of the resonator decreases the thresholds of many power-dependent nonlinear optical effects, especially the stimulated Rayleigh scattering (STRS) and the stimulated Brillouin scattering (SBS). Of course, these two nonlinear optical phenomena are of interest for many applications [9] - [12]. Moreover, it has been demonstrated in [13] that the SBS can be very useful to create an all-optical tunable OEO.…”
Section: Introductionmentioning
confidence: 99%
“…More investigations on the generation of different nonlinear optical effects inside the FRR have been performed and will be published elsewhere [16]. In addition, we have successfully demonstrated that the SBS process inside the FRR can be used as selective optical amplification to generate high power and high spectral purity millimeter wave signals above 65 GHz [17].…”
Section: Noise In the Resonator-based Oeomentioning
confidence: 99%